Higher order compact-flowfield dependent variation (HOC-FDV) solution of one-dimensional problems - Elfaghi, Abdulhafid M.; Asrar, Waqar; Omar, Ashraf Ali (The Hong Kong Polytechnic University, 2010)
In this paper, a novel higher order accurate scheme, namely high order compact flowfield dependent variation (HOC-FDV) method has been used to solve one-dimensional problems. The method is fourth order accurate in space and third order accurate in time. Four numerical problems; the nonlinear viscous Burger’s equation, transient Couette flow, the shock tube (Sod problem) and the interaction of two blast waves are solved to test the accuracy and the ability of the scheme to capture shock waves and contact discontinuities. The solution procedure consists of tri-diagonal matrix operations and produces an efficient solver. The results are compared with analytical solutions, the original FDV method, and other standard second order methods. The results also show that HOC-FDV scheme provides more accurate results and gives excellent shock capturing capabilities.